2019
DOI: 10.1155/2019/1025032
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Central Venous Catheter-Related Bloodstream Infections: Evaluation of Bundle Prevention in Two Intensive Care Units in Central Brazil

Abstract: Background Central venous catheter-associated bloodstream infections (CVC-BSIs) have been associated with increased length of hospital stay, mortality, and healthcare costs, especially in intensive care units (ICUs). The aim of this study was to evaluate the incidence density of CVC-BSIs before and after implementation of the bundle in a hospital of infectious and dermatological diseases in Central Brazil. Methods A retrospective cohort study was conducted in two ICUs (adult and pediatric) between 2012 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Quanto as complicações associadas a cateteres venosos centrais, estudo apontou aquelas ocorridas durante a inserção do cateter como o hematoma, e principalmente, as infecções causadas por Staphylococcus epidermidis e Staphylococcus aureus em unidades de terapia intensiva 14 .…”
Section: Discussionunclassified
“…Quanto as complicações associadas a cateteres venosos centrais, estudo apontou aquelas ocorridas durante a inserção do cateter como o hematoma, e principalmente, as infecções causadas por Staphylococcus epidermidis e Staphylococcus aureus em unidades de terapia intensiva 14 .…”
Section: Discussionunclassified
“…The prevalence of NIs due to K. pneumoniae has been reported to be approximately 10% worldwide [173]. Several studies revealed the implication of K. pneumoniae in HAIs, especially in catheter-related infections (CRIs) [18,85,172,[174][175][176][177][178][179]. Since this bacterium is commensal in humans, gastrointestinal colonization represents the major source of transmission and the development of infections towards other sites [180].…”
Section: Klebsiella Pneumoniaementioning
confidence: 99%
“…All were performed in only one establishment providing health services. In one of the studies (YOSHIDA et al, 2019), the research focus was BSI associated with the central venous catheter, where the ID was 3.4 per 1,000 CVC-day in an adult ICU, lower than that presented by the ECDC regarding Italy, where the BSI rate associated with the central venous catheter was 4.8 per 1,000 CVC-day, and significantly higher than the rates of 1.7 per 1,000 CVC-day reported in the same ECDC report (2019) for countries such as Portugal and Luxembourg (ECDC, 2019). The other publications included in this review pointed to the occurrence of BSIs in specific contexts such as BSIs caused by Candida spp.…”
Section: Developmentmentioning
confidence: 99%
“…(CANELA et al, 2017), ICS in adult transplant patients (FERREIRA et al, 2018;CHUEIRI NETO et al, 2019); Hospital sepsis in adult patients (WESTPHAL et al, 2019), lateonset BSI in neonates (FREITAS et al 2019), making the correlation with multicentric publications unfeasible. The populations that composed the studies had numbers ranging from 11,465 CVC-days (YOSHIDA et al, 2019) to 79 patients (CANELA et al, 2017).…”
Section: Developmentmentioning
confidence: 99%